2004
DOI: 10.1038/sj.bjp.0705873
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c‐Jun N‐terminal kinase decreases cardiomyocyte apoptosis and infarct size after myocardial ischemia and reperfusion in anaesthetized rats

Abstract: 1 Myocardial ischemia/reperfusion is associated with inflammation, apoptosis and necrosis. During this process, c-jun N-terminal kinase is activated in cardiac myocytes resulting in apoptosis. 2 This study investigates the effects of AS601245, a nonpeptide ATP competitive JNK inhibitor, on infarct size caused by myocardial ischemia/reperfusion in anaesthetized rats. The left descending coronary artery of anaesthetized rats was occluded for 30 min and then reperfused for 3 h. AS601245 was administered 5 min bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 24 publications
7
90
2
3
Order By: Relevance
“…Through the use of a newly developed JNK-selective inhibitor or antisense oligoes, JNK activity was shown to play an important role in myocyte apoptosis after ischemia/reperfusion. 91,92 In contrast, a number of other studies demonstrated a critical role for JNK in myocyte survival and cardioprotection. 89 96,97 However, other prosurvival pathways, including AKT, also are targeted by JNK.…”
Section: Jnk Pathway In Cardiomyocyte Death Regulationmentioning
confidence: 82%
“…Through the use of a newly developed JNK-selective inhibitor or antisense oligoes, JNK activity was shown to play an important role in myocyte apoptosis after ischemia/reperfusion. 91,92 In contrast, a number of other studies demonstrated a critical role for JNK in myocyte survival and cardioprotection. 89 96,97 However, other prosurvival pathways, including AKT, also are targeted by JNK.…”
Section: Jnk Pathway In Cardiomyocyte Death Regulationmentioning
confidence: 82%
“…Ischemia-reperfusion-Multiple studies have shown that pharmacological inhibition of JNK-1 reduces myocardial infarction and apoptosis in animal models of AMI (13,21,22,24). However, it is not possible to attribute an exclusive death-promoting role for JNK-1 because of other reports that JNK can be protective (20, 24 -27).…”
Section: Jnk-1 Protects Against Acute Injury During Briefmentioning
confidence: 91%
“…Akt regulates multiple survival pathways that collectively repress mitochondrial death channels and its inactivation by JNK after extended ischemia results in the loss of this protection. Inhibition of Akt by JNK-1 in this setting may account for as much as 50% of reperfusion-mediated infarction (21,22). When the period of ischemia is brief, ROS and kinase pathways are still activated by reperfusion, but ATP levels are maintained, and the role of JNK-1 is reversed.…”
Section: Jnk Protects Cardiac Myocytes Against Hypoxia Reoxygenation mentioning
confidence: 99%
“…By contrast, JNK inhibitors have been proposed to prevent cell death associated with stroke and myocardial infarction (21,46). It is also likely that JNK inhibition may prevent ischemia-induced edema, which has also been linked to abnormal VEGF production (47).…”
Section: Discussionmentioning
confidence: 99%